(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
In this article, Our President Sh. Mirziyoev expressed his opinion on the implementation of new reforms in the New Uzbekistan in the address to the Supreme Assembly and people dated 22.12.2022.